Heterogeneous photocatalysis of sulfonamides using TiO2 and ZnO photocatalysts with mercury-vapor and led light sources - Náfrádi Máté; Farkas Gellért; Vas Benjámin; Alapi Tünde; International Symposium on Analytical and Environmental Problems (26.) (2020) (Szeged) (2020)
Sulfonamides are one of the most often used antibiotics worldwide. The spread of antibioticresistant bacteria and the serious health problems caused by them justify the importance of removing antibiotics and their metabolites from water. Heterogeneous photocatalysis is one of the promising methods for elimination of trace organic pollutants from water. This work aims at the investigation of heterogeneous photocatalytic removal of two sulfonamide antibiotics, sulfamethazine and sulfamethoxypyridazine. Commercially available TiO2 and ZnO were used as photocatalysts, and a mercury vapor lamp (300-400 nm) and UV-LEDs (398 nm) were used as light sources. The efficiency and cost-effectiveness of heterogeneous photocatalysis in the removal of sulfonamides were compared, using TiO2 and ZnO, in suspensions irradiated with mercury vapor lamp and LEDs. The mercury vapor lamp was found to be more effective due to the better utilization of UV light by the photocatalysts. The LED light source was also worse in terms of operating costs, and TiO2 with mercury vapor lamps was the most efficient at removing the total organic carbon content.
Keywords: Természettudományok; Kémiai tudományok